Operation control and generation optimization of grid-connected distributed energy sources - Chew, Kean Lim. (2011)
Unit commitment and economic dispatch, when integrated together, is a powerful tool to obtain the most economical generation schedule with which demand and spinning reserve requirement are met, and all generating unit constraints such as unit minimum and maximum generation capabilities, and unit minimum up-time and down-time, are satisfied over a time horizon. Adaptive Lagrangian Relaxation (ALR), Unit Decommitment, Priority List (PL) and lambda-iteration methods are consolidated in this report to search for the optimal unit commitment and economic dispatch schedule. An optimization algorithm to include Energy Storage System (ESS) and to operate the Intelligent Energy Distributed System (IEDS) as a grid-connected system is also proposed. This allows the system to coordinate the usage and storage of energy for peak shaving and to trade the energy stored with the grid. The proposed routine is also able to maximize the system profit related to its own generation, to meet various time-of-use-rate schemes and to take advantage of the grid whenever the grid offers a cheaper source of electricity supply. The hybrid commitment solution used in the project in a nutshell yields short-term scheduling result in the responsive seconds and is favorable for large-scale implementation.